Classification and challenges in the histopathological diagnosis of peripheral T-cell lymphomas, emphasis on the WHO-HAEM5 updates - Murga-Zamalloa, Carlos; Inamdar, Kedar (Frontiers in Oncology, 2022)
Mature T-cell lymphomas represent neoplastic expansions of T-cell lymphocytes with a post-thymic derivation. Most of these tumors feature aggressive clinical behavior and challenging histopathological diagnosis and classification. Novel findings in the genomic landscape of T-cell lymphomas are helping to improve the understanding of the biology and the molecular mechanisms that underly their clinical behavior. The most recent WHO-HAEM5 classification of hematolymphoid tumors will incorporate novel molecular and histopathological findings that will aid in the diagnostic classification of this group of neoplasms. The current review article summarizes the most relevant diagnostic features of peripheral T-cell lymphomas with an emphasis on the updates that are incorporated at the WHO-HAEM5.